If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -1(-12) = X Multiply -1 * -12 -5 + 12 = X Combine like terms: -5 + 12 = 7 7 = X Solving 7 = X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 7 + -1X = X + -1X Combine like terms: X + -1X = 0 7 + -1X = 0 Add '-7' to each side of the equation. 7 + -7 + -1X = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1X = 0 + -7 -1X = 0 + -7 Combine like terms: 0 + -7 = -7 -1X = -7 Divide each side by '-1'. X = 7 Simplifying X = 7
| 2-b=23 | | x^3+4x^2-25x-100=0 | | 12x-5(x-6)=7x+5 | | 4(4c-1)-2=14c+2 | | 8(3x-2)=4(6x+9) | | -3(t+1)=12 | | 2.5x+10=7.5 | | -2x-6=-22 | | -78=-30+6x | | 2(2x+8)=2(3x+6) | | 33-18=3(x-2) | | 2x^4-7x^3+14x^2-28x+24=0 | | 24+5y-7=16y-10-2y | | d^2+18(d+4)=9 | | 3(2n-4)=(8n+6)+9 | | 35+11x=2x-100 | | -84=-8+2(8p-6) | | x^2=4x+12 | | x+19+4x=-41-4x-48 | | 59=-51+10x | | 36x^2-54x-360=0 | | -12x-20=-10x+100 | | 8y+3(y-5)=4(y+1)-2 | | 18.10x=63.35 | | 17-6x=9+2x | | x^3+5x^2+7x-8=0 | | 3x-3(5x+4)=-72 | | 1.6=18.10x | | 8-7(-8r-2)=-426 | | 5x-5=6x+8 | | -9y= | | 7v*2-9v= |